The interaction of tide and river flow on water quality in Hai Phong coastal waters (Lach Huyen - Do Son) drawn from field observation - Vu , Thanh Ca; Mai , Van Tien; Nguyen, Bich Ngoc; Nguyen , Khac Doan; Hoang , Truong (Vietnam Journal of Marine Science and Technology, 2023)
This paper presents the results of a study on the impacts of the interaction of tide and river flow on water quality at the Hai Phong coastal water, outside the Nam Trieu estuary and Lach Huyen, drawn from field observation from October 14, 2022, to October 17, 2022. During the field observation, the dissolved oxygen concentration was measured, and water samples were taken at the surface, mid-depth, and bottom of 8 observational points at 1:00, 7:00, 13:00, and 19:00 h. Five sewage wastewater samples at Do Son coast and 6 coastal and river water samples were also taken. The collected seawater samples were laboratory analyzed to determine the concentration of BOD5, COD, TN, and TP. Additionally, the concentration of ions NH4+, NO2-, NO3-, and PO43- are determined by analyzing collected coastal, river, and sewage water samples and seawater samples at mid-depth at all observational points in a laboratory. It was found that the concentration of essential nutrients and other environmental components in wastewater samples generally does not exceed those specified in Vietnam regulations. The discharge of wastewater during the field observation was minimal. Thus it could be expected that the wastewater would not have a notable influence on seawater quality in the marine study area. Consequently, the study area’s primary source of nutrient pollutants was rivers. Time variation of the concentration of environmental components reveals that the nutrient concentration in the marine study area strongly influences by the interaction of the tide and river flow. The concentration of dissolved oxygen and major nutrient components in seawater at 8 points was within the limit of Vietnam standard for coastal water. However, significant nutrient concentration exceeds thresholds for eutrophication.